Evaluation of Antimicrobial Activity of Cuminum Cyminum Essential Oil and Extract against Bacterial Strains Isolated from Patients with Symptomatic Urinary Tract Infection - Saee, Yasaman; Dadashi, Masoud; Eslami, Gita; Goudarzi, Hossein; Taheri, Soudabeh; Fallah, Fatemeh (Novelty in Biomedicine, 2016)
Background: Many efforts have been done to find effective agents against resistant pathogens. Cuminum cyminum L. (Cumin) is an aromatic plant within the Apiaceae family. It has a variety of purposes and demonstrates antimicrobial and antioxidant properties. This study evaluated the activity of C. cyminum extract and essential oil against bacterial isolates which cause urinary tract infection, including Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Streptococcus agalactiae, group A streptococci, Enterococcus faecalis, Staphylococcus epidermidis, Staphylococcus aureus and Staphylococcus saprophyticus isolated from patients with urinary tract infection. Materials and Methods: Extract was prepared by maceration and essential oil was prepared by hydrodistillation from C. cyminum seeds. The study population was 95 patients with urinary tract infection without malignant diseases, diabetes and immunosupression. After identification of organism, susceptibility testing was carried out by disc diffusion method and MIC values by broth microdilution testing. Results: C. cyminum essential oil can have a better effect on the gram-negative bacteria causing urinary tract infection than gram-positive bacteria. In addition, C. cyminum extract have good activity against both gram- positive and gram-negative bacteria. Our findings also showed that essential oil and extract of C. cyminum has better antibacterial activity on uropathogen isolates than amoxicillin and the difference was significant (P value<0.05) but the activity is not superior to other antibiotics. Conclusion: These results suggest that the essential oil and extract of C. cyminum seeds might be considered as interesting sources of antibacterial components against uropathogenic bacteria.